Pelatihan Cara Pengolahan Pangan Olahan Yang Baik (CPPOB) Pada Unit Produksi Di SMK Negeri 1 Sungai Raya - Panca Wardanu, Adha; Uliyanti, Uliyanti (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
This Community Service Program (CSP) aims to enhance the understanding and skills of production unit managers and students regarding Good Manufacturing Practices (GMP) to uphold the quality, safety, and competitiveness of products produced by the SMK N 1 Sungai Raya production unit. The CSP activities involve GMP training and mentoring, engaging 16 students, one production unit coordinator, and one teacher. Conducted at the production unit at SMK N 1 Sungai Raya, the implementation includes preparation, execution, and evaluation stages. Participants exhibited high enthusiasm during the GMP training, attentively absorbing the material presented by the community service team. The outcomes of this activity have improved participants' understanding of GMP principles and their skills in applying GMP aspects in food processing production. Overall, the CSP successfully assisted the production unit of SMK N 1 Sungai Raya in enhancing product quality, safety, and competitiveness through increased knowledge of managers and students regarding GMP principles in food production processes.